FORMATION AND FUNCTIONAL CHARACTERISTICS OF PHRASEOLOGISMS IN UZBEK LANGUAGE - Narmuratov Zayniddin Radjabovich (Web of Journals Publishing, 2023)
This article deals with some issues of studying the phraseology of Turkic languages, the history of the study of Uzbek phraseology and phraseography were briefly reviewed.
Keywords: phrase, phraseologism, phraseological formation, phraseology, fixed phrase, idiom, phraseology and phraseography.